Effect of computerized prescriber order entry on pharmacy: Experience of one health system. - Mcmullen, Carmit K.; Macey, Tara A.; Pope, Jill; Gugerty, Brian; Slot, Marti; Lundeen, Peter; Ash, Joan; Carlson, Neil (American Journal of Health-System Pharmacy, 2015)
positive expectations about CPOE prior to and during system implementation and continued to hold positive views about CPOE after several months of system use. In interviews and focus group discussions, pharmacists reported a number of important CPOE benefits, but they also cited challenges related to CPOE provider alerts, uncertainty about medication timing, and the need to support providers by serving as informal CPOE system trainers. Direct observation of pharmacists before and after CPOE implementation indicated decreases in both the rate of order clarification events (from 0.89 to 0.35 per hour, p < 0.001) and the average time spent per hour clarifying orders (from 4.75 to 2.11 minutes, p = 0.008). Conclusion Several months after CPOE implementation, pharmacists indicated that several aspects of their workload had improved, including the process of medication order clarification, their ability to prioritize work, and their ability to move around within the hospital to respond to demand. However, pharmacists also noted that order ambiguity still existed and that the system needed to be optimized to gain efficiencies and increase clarity.